Let the function g(a, b) = f(a) + f(b).

For which function f below will g(a + b, a + b) = g(a, a) + g(b, b)?

X+3

X^2

|X|

1/X

X/4

## How to solve these FUNCTIONS?

##### This topic has expert replies

### GMAT/MBA Expert

- [email protected]
- GMAT Instructor
**Posts:**3835**Joined:**02 Apr 2010**Location:**Milpitas, CA**Thanked**: 1854 times**Followed by:**523 members**GMAT Score:**770

g(a + b, a + b) = f(a + b) + f(a + b) = 2*f(a + b)himu wrote:Let the function g(a, b) = f(a) + f(b).

For which function f below will g(a + b, a + b) = g(a, a) + g(b, b)?

g(a, a) = f(a) + f(a) = 2*f(a)

g(b, b) = f(b) + f(b) = 2*f(b)

Hence, we need to find a function which satisfies the condition 2*f(a + b) = 2*f(a) + 2*f(b), i.e. f(a + b) = f(a) + f(b)

This relation will satisfied only by linear functions.

Hence, only possible options are (A) f(x) = x + 3 or (C) f(x) = |x| or (E) f(x) = x/4

For option (A) ---> f(a + b) = (a + b + 3) â‰ f(a) + f(b) = (a + 3) + (b + 3) = (a + b + 6)

For option (C) ---> f(a + b) = |a + b| may not be equal to f(a) + f(b) = |a| + |b|

For option (E) ---> f(a + b) = (a + b)/4 = f(a) + f(b) = a/4 + b/4 = (a + b)/4

The correct answer is E.

Anurag Mairal, Ph.D., MBA

GMAT Expert, Admissions and Career Guidance

Gurome, Inc.

1-800-566-4043 (USA)

Join Our Facebook Groups

GMAT with Gurome

https://www.facebook.com/groups/272466352793633/

Admissions with Gurome

https://www.facebook.com/groups/461459690536574/

Career Advising with Gurome

https://www.facebook.com/groups/360435787349781/

GMAT Expert, Admissions and Career Guidance

Gurome, Inc.

1-800-566-4043 (USA)

Join Our Facebook Groups

GMAT with Gurome

https://www.facebook.com/groups/272466352793633/

Admissions with Gurome

https://www.facebook.com/groups/461459690536574/

Career Advising with Gurome

https://www.facebook.com/groups/360435787349781/

- GMATGuruNY
- GMAT Instructor
**Posts:**15532**Joined:**25 May 2010**Location:**New York, NY**Thanked**: 13060 times**Followed by:**1897 members**GMAT Score:**790

We can plug in values.Let the function g(a, b) = f(a) + f(b).

For which function f below will g(a + b, a + b) = g(a, a) + g(b, b)?

A: x+3

B: x^2

C: |x|

D: 1/x

E: x/4

OA : x/4

Since one of the answer choices is |x|, we should plug in at least one negative value.

Let a=-2 and b=3.

Then a+b = -2+3 = 1.

The question becomes:

*For which function f below will g(1, 1) = g(-2, -2) + g(3, 3)?*

Since g(a,b) = f(a) + f(b):

g(1,1) = f(1) + f(1) = 2f(1)

g(-2,-2) = f(-2) + f(-2) = 2f(-2)

g(3,3) = f(3) + f(3) = 2f(3)

Substituting these relationships into g(1,1) = g(-2,-2) + g(3,3), we get:

2f(1) = 2f(-2) + 2f(3)

f(1) = f(-2) + f(3).

Thus, the question now becomes:

*For which function f below will f(1) = f(-2) + f(3)?*

**A: x+3**

f(1) = 1+3 = 4.

f(-2) + f(3) = (-2+3) + (3+3) = 10.

Doesn't work. Eliminate A.

**B: xÂ²**

f(1) = 1Â² = 1.

f(-2) + f(3) = (-2)Â² + 3Â² = 13.

Doesn't work. Eliminate B.

**C: |x|**

f(1) = |1| = 1.

f(-2) + f(3) = |-2| + |3| = 5.

Doesn't work. Eliminate C.

**D: 1/x**

f(1) = 1/1 = 1.

f(-2) + f(3) = -1/2 + 1/3 = -1/6.

Doesn't work. Eliminate D.

The correct answer is E.

**E: x/4**

f(1) = 1/4

f(-2) + f(3) = -2/4 + 3/4 = 1/4.

Success!

Mitch Hunt

Private Tutor for the GMAT and GRE

[email protected]

If you find one of my posts helpful, please take a moment to click on the "UPVOTE" icon.

Available for tutoring in NYC and long-distance.

For more information, please email me at [email protected].

Student Review #1

Student Review #2

Student Review #3

Private Tutor for the GMAT and GRE

[email protected]

If you find one of my posts helpful, please take a moment to click on the "UPVOTE" icon.

Available for tutoring in NYC and long-distance.

For more information, please email me at [email protected].

Student Review #1

Student Review #2

Student Review #3

first of all, this q. is well beyond GMAT

secondly, the main trick here is that all q. choices contain only one variable (it doesn't matter what it states a or b or a+b, we speak about the number of variables), but the target function,

Just before moving, try to understand some more ...

g(a, b) = f(a) + f(b) What does it tell us?

It tells that the function of

g(a + b, a + b) = g(a, a) + g(b, b) What does it tell us?

It tells us that two-variable function of

The last part in the preceding sentence is important, as we see that the function of two variables, g(a + b, a + b), behaves the way as the first function g(a, b) = f(a) + f(b) does.

So,

We already know g(a + b, a + b)= g(a, a) + g(b, b) which is equivalent to 2f(a+b)=2f(a)+2f(b)

a) X+3 and f(a+b)=f(a)+f(b). Let f(a+b) be f(x) then f(a+b)=a+b+3, because f(x)=x+3.

We check further, Let f(a) be f(x), then f(a)=a+3 and the same with f(b)=b+3. So, f(a+b)=f(a)+f(b) is equivalent to a+b+3=a+3+b+3. Obviously, this is false, since a+b+3=!a+b+6

b) X^2. Let f(a+b) be f(x) then f(a+b)=(a+b)^2 and with the same logic f(a)=a^2 and f(b)=b^2. We check whether f(a+b)=f(a)+f(b), (a+b)^2=a^2+b^2? No, this is false

c) |X|. Let f(a+b) be f(x) then f(a+b)=|a+b|, accordingly, f(a)=|a| and f(b)=|b|. Is |a+b|=|a|+|b|? No, false

d) 1/X. Let f(a+b) be f(x) then f(a+b)=1/(a+b), consequently, f(a)=1/a and f(b)=1/b. We check if 1/(a+b)=1/a +1/b? No, false

e) X/4. Let f(a+b) be f(x) then f(a+b)=(a+b)/4, also f(a)=a/4 and f(b)=b/4. We may check if (a+b)/4=a/4+b/4. Yes, indeed.

p.s. I have decided to give detailed explanation for this q. because the solution by Anurag was in PhD style and the solution by Mitch was as usually intuitive, plug and check.

secondly, the main trick here is that all q. choices contain only one variable (it doesn't matter what it states a or b or a+b, we speak about the number of variables), but the target function,

**For which function f below will g(a + b, a + b) = g(a, a) + g(b, b)?**contains two variables in one function of the left-hand-side and right-hand-side. This is why we must simplify this function to contain one variable on both sides. We will do it with the help of given function**g(a, b) = f(a) + f(b)**Just before moving, try to understand some more ...

g(a, b) = f(a) + f(b) What does it tell us?

It tells that the function of

*two variables a and b*varies as the sum of*one-variable*functionsg(a + b, a + b) = g(a, a) + g(b, b) What does it tell us?

It tells us that two-variable function of

*two identical variables (a+b) and (a+b)*varies as the sum of two*two-variable*functionsThe last part in the preceding sentence is important, as we see that the function of two variables, g(a + b, a + b), behaves the way as the first function g(a, b) = f(a) + f(b) does.

So,

**g(a,a)**=f(a)+f(a) and**g(b,b)**=f(b)+f(b)*OR*g(a,a)=2f(a) and g(b,b)=2f(b). The same way,**g(a+b, a+b)**=f(a+b)+f(a+b)=2f(a+b)We already know g(a + b, a + b)= g(a, a) + g(b, b) which is equivalent to 2f(a+b)=2f(a)+2f(b)

*OR*f(a+b)=f(a)+f(b). This means we have simplified two-variable function and set it as one-variable function actually. We can begin checking with the variable xa) X+3 and f(a+b)=f(a)+f(b). Let f(a+b) be f(x) then f(a+b)=a+b+3, because f(x)=x+3.

We check further, Let f(a) be f(x), then f(a)=a+3 and the same with f(b)=b+3. So, f(a+b)=f(a)+f(b) is equivalent to a+b+3=a+3+b+3. Obviously, this is false, since a+b+3=!a+b+6

b) X^2. Let f(a+b) be f(x) then f(a+b)=(a+b)^2 and with the same logic f(a)=a^2 and f(b)=b^2. We check whether f(a+b)=f(a)+f(b), (a+b)^2=a^2+b^2? No, this is false

c) |X|. Let f(a+b) be f(x) then f(a+b)=|a+b|, accordingly, f(a)=|a| and f(b)=|b|. Is |a+b|=|a|+|b|? No, false

d) 1/X. Let f(a+b) be f(x) then f(a+b)=1/(a+b), consequently, f(a)=1/a and f(b)=1/b. We check if 1/(a+b)=1/a +1/b? No, false

e) X/4. Let f(a+b) be f(x) then f(a+b)=(a+b)/4, also f(a)=a/4 and f(b)=b/4. We may check if (a+b)/4=a/4+b/4. Yes, indeed.

p.s. I have decided to give detailed explanation for this q. because the solution by Anurag was in PhD style and the solution by Mitch was as usually intuitive, plug and check.

himu wrote:Let the function g(a, b) = f(a) + f(b).

For which function f below will g(a + b, a + b) = g(a, a) + g(b, b)?

X+3

X^2

|X|

1/X

X/4

Success doesn't come overnight!